The Effects of Climate Change on Landscape Connectivity and Genetic Clusters in a Small Subtropical and Warm-Temperate Tree - Guan, Bicai; Gao, Jingjing; Chen, Wei; Gong, Xi; Ge, Gang (Frontiers in Plant Science, 2021)
Climate change is a great threat to global biodiversity and has resulted in serious ecological consequences. Though the potential effects of climate changes on genetic diversity have recently received much research attention, little research has focus on the impacts of climate changes on genetic connectivity and the relationship between the climate stability and genetic divergence. Here, we combined the population connectivity with genetic data to predict the impacts of future climate change on genetic connectivity. Coupled climatic variables and genetic data, we used POPS software to create spatially explicit simulations and predict the dynamics in genetic clusters in response to climate changes. A generalized additive model was employed to test the correlation between climatic stability and genetic diversification. Our findings indicated that a reduction in species distribution due to severe climate changes would lead to substantial loss of genetic connectivity. More severe future climatic scenarios would likely cause greater loss of variability or more distinct homogenization in genetic variation of species. Relatively low interpolated genetic distances are generally associated with areas of greater losses in climatic suitability from the present to the future. The displacement of climatic genetic clusters will challenge species adaptation to future climate changes due to loss of fundamental evolutionary potential. The plant species’ persistence capacity may be weakened in the face of future climate changes.